Arte sonora: nomadismo, escutas e processos criativos - Ramos, Alex Suraty (Universidade Federal de São Carlos, 2022)
The present work proposes to investigate the poetic aspects intrinsic to the Sound Art, taking the nomadism notion as the principal reference. Starting from the relationship between the pieces, the listening modes and the interactive processes, the dissertation approaches how the choices of materials, technologies and the formation of sound artists are important elements in the creative process. The sound artist transits between different means, knowledges, technologies and art languages to propose their own pieces. This research conducts a mapping of píeces and sound artists, tracing a broad dialogue with the investigated bibliography. The researched Sound Art pieces are found as sound installations, site-specific, sound sculptures and interactive environments. The Sound Art explores the potential of listening and the use of sound as a way of interacting with the pieces. In this way, the research points out that this artistic genre is characterized by its hybridism, revealing some historical approximations between music and the contemporary plastic arts. Furthermore, it is of great importance for the conception of Sound Art the influence of the experimental pieces of John Cage and the Fluxus group. From Cox's theory (2004; 2009) about the notions of becoming and duration, the virtual and the actual; and from Santos's theory (2000; 2004; 2006) about nomadic listening, it was concluded that Sound Art enables a listening in movement, dialoguing with the spectator’s memories on aesthetic enjoyment in sculptures, installations and architectonic spaces. So the sound artist is observed as a proposer of pieces and the creation arises from experiences in process.
Sound Art; nomadism, listening and creative processes
Keywords: Arte sonora; Artista-propositor; Escuta nômade; Instalação sonora; Processos criativos; Sound Art; Artist-proposer; Nomadic listening; Sound Installation; Creative processes; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES PLASTICAS; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA